Relações em rede: um estudo de caso da Ordem DeMolay - Fostinone Netto, Luiz (2017)
The present work is an explanation of social networks and personal interactions, or flow of information within a group. The study object to the DeMolay Order of the state of São Paulo. The objective is to verify if the DeMolay Order has a social network and to identify a main tool used in the communication of the actors of the network. For data collection, a questionnaire created in Google Doc was used. Responses were treated without Excel 2016 software and transferred to the NodeXL software to generate the graphs and notes, which allowed the information to cross over members of the DeMolay Order and its frequency of communication. The objective of the research was reached with a finding that the DeMolay Order of the state of São Paulo forms a network and its main communication tool is the instant messaging application of cellular handsets called WhatsApp